OPTIMIZATION OF ZAKAT RECEIVING THROUGH THE DIGITAL PLATFORM AT THE ZAKAT MANAGEMENT FOUNDATION IN SURABAYA - Erwan Aristyanto; Agus Sarwo Edi (Jurnal Ilmiah Satyagraha, 2023)
This study aims to determine and describe the influence of religiosity and service quality on people's interest and decision to pay zakat through digital platforms. The research uses quantitative research methods. The population in this study is all people who pay zakat through a digital platform with a sample of 97 respondents. Data collection techniques using the method of observation, interviews, documentation and other data. Data analysis uses SPSS analysis with the aim of testing the religiosity variable, service quality variable, community decision variable to pay zakat through digital platforms and public interest in paying zakat through digital platforms. The results of this study indicate that the religiosity variable and service quality variable greatly influence the interest and decision of the community to pay zakat through digital platforms because it makes it easier for people to pay zakat which can be done anytime and anywhere.